A k-core decomposition-based opinion leaders identifying method and clustering-based consensus model for large-scale group decision making. (December 2020) - Gao, Pengqun; Hung, Jing; Xu, Yejun
Highlights: A clustering method is provided for dividing DMs into different clusters. A k -core decomposition algorithm along with SNA process is proposed to identify opinion leaders of each cluster. A cluster-based consensus model is presented. Abstract: Due to the development of network technology, large-scale group decision making (LSGDM) has become increasingly concerned. In this paper, a k -core decomposition-based opinion leaders identifying method and clustering-based consensus model are developed for LSGDM problems. Firstly, a clustering method based on similarity degree is provided for dividing decision makers (DMs) into several clusters. Then, sub-clusters are presented for social networks (SNs) construction process, which are consist of DMs with same alternative ranking information. Furthermore, a novel k -core decomposition-based opinion leaders identifying method is proposed for selecting opinion leaders of these SNs. Finally, the opinion leaders identified are applied to the following clustering-based consensus model in LSGDM. The weights of DMs are distributed appropriately and the group can efficiently reach a consensus based on the proposed social network analysis (SNA) methods and consensus reaching process (CRP). A case study on flood disaster management shows that the proposed methods are feasible for LSGDM problems.